UPAYA MENCEGAH PENYAKIT GIGI MELALUI PERAN KELOMPOK TUTOR SEBAYA PADA MURID SD N 2 KEROBOKAN KAJA KECAMATAN KUTA UTARA KABUPATEN BADUNG TH 2022 - Ratmini, Ni Ketut; Arini, Ni Wayan (Poltekkes Kemenkes Denpasar, 2024)
The problem of cavities is still a lot of complaints by both children and adults and cannot be allowed to get worse, because it will affect the quality of life where they will experience pain, discomfort, disability, acute and chronic infections, eating and sleeping disorders and have a high risk of hospitalized, which leads to high medical expenses and reduced time spent at school. Peer tutors have an important role in learning activities. In peer tutoring, the term tutor is used for students who act as teachers, while tutee is used for students who have learning difficultiesThe dedication method is to form a group of tutors from each class, then through the tutor carry out promotive and preventive activities in the form of counseling on how to maintain dental hygiene to the tutor to continue inviting them to practice brushing their teeth. The objects (target audience) were 158 students at SD N 2 Kerobokan Kaja, consisting of students from grades three to grades five. The results achieved in community service at SD N 2 Kerobokan Kaja are 1). Increased knowledge about maintaining dental and oral hygiene for students of SD N 2 Kerobokan Kaja, North Kuta District, Badung, from an average score of 63 before the service was carried out and to an average of 85 after the service was carried out. The conclusion from this community service activity is that the role of the tutor group can help increase knowledge about how to maintain dental hygiene and improve teeth brushing skills for elementary school students.